Relationship Between Visual Field Sensitivity and Retinal Nerve Fiber Layer Thickness Measured by Scanning Laser Polarimetry and Optical Coherence Tomography in Normal, Ocular Hypertensive and Glaucomatous Eyes - Lleó-Pérez, Antonio (2010)
PURPOSE: To evaluate the correlation between automated achromatic perimetry (AAP) and the output of two retinal nerve fiber layer (RNFL) analysers: scanning laser polarimetry (GDx-VCC) and optical coherence tomography (OCT). METHODS: Quantitative RNFL measurements with GDx-VCC and Stratus-OCT were obtained in one eye from 52 healthy subjects, 38 ocular hypertensive (OHT) patients and 94 glaucomatous patients. All patients underwent a complete examination, including AAP using the Swedish interactive threshold algorithm (SITA). The relationship between RNFL measurements and SITA visual field global indices were assessed by means of the following methods: analysis of variance, bivariate Pearson's correlation coefficient, multivariate linear regression techniques and nonlinear regression models, and the coefficient of determination (r(2)) was calculated. RESULTS: RNFL thickness values were significantly lower in glaucomatous eyes than in healthy and ocular hypertensive eyes for both nerve fiber analysers (P≤0.001), except for the inferior 120° average thickness in GDx-VCC. Linear regression models constructed for GDx-VCC measurements and OCT-derived RNFL thickness with SITA visual field global indices demonstrated that, for the mean deviation, the only predictor in the model was the nerve fiber indicator for GDx-VCC (r(2)=0.255), and for the pattern standard deviation, the predictors in the model were the nerve fiber indicator for GDx-VCC (r(2)=0.246) and the maximum thickness in the superior quadrant for Stratus-OCT (r(2)=0.196). The best curvilinear fit was obtained with the cubic model. CONCLUSIONS: Quantitative measurements of RNFL thickness using either GDx-VCC or OCT correlate moderately with visual field global indices in moderate glaucoma patients. We did not find a correlation between visual field global indices and RNFL thickness in early glaucoma patients. Further study is needed to develop new analytical methods that will increase RNFL analyser's sensitivity in early glaucoma patients.